To study the knowledge about the handling of biomedical waste among health-care workers in a COVID-19 hospital setting - Sukhbir Singh; Vrinda Tom; Ramesh Verma; Ishwanti Malik; Madan Gopal Vashist; Pushpa Dahiya (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The unexpected increase in COVID-19-related waste and its inappropriate disposal had blown up the threat of retransmission of this infection and adversely impacted the environment. The aim of this study was to evaluate the existing knowledge about the handling of biomedical waste (BMW) in the COVID-19 Hospital setting among health-care workers (HCWs). MATERIALS AND METHODS: It was a prospective cross-sectional study done for 3 months, i.e., October 2020-December 2020 among nursing professionals across all seniority posted in COVID hospital. A pretested questionnaire comprised 20 questions was used as a study tool. RESULTS: The response rate of our study was 94%. The mean age of respondents was 33.97 years, and the mean length of service was 8.32 years. The study revealed that the respondents had a mean knowledge score of 12.21 (Median 12, standard deviation 2.129 and 95% confidence interval of 11.92-12.51). CONCLUSIONS: There is consensus among the researchers/scholars that COVID-BMW hazards are much more significant than regular BMW. Therefore, its awareness among the HCWs can be a panacea for safer handling of BMW generated in COVID Hospital.